2013
DOI: 10.1007/s11748-013-0322-5
|View full text |Cite
|
Sign up to set email alerts
|

A successful treatment for concomitant injury of the coronary artery and tricuspid valve after blunt chest trauma

Abstract: A 63-year-old woman involved in an automobile accident was brought to our hospital with thoracic injury sustained by the impact of her vehicle's steering wheel. Cardiac auscultation revealed a grade III/VI systolic murmur and the electrocardiogram showed ST elevation in leads 2, 3 and aVF. A 2D echocardiogram revealed severe tricuspid regurgitation and a hypokinetic right ventricle. Coronary angiography revealed dissection of the proximal right coronary artery (RCA) with 90 % stenosis. Urgent CABG for the RCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In the review of five surgical cases reported in Japan from 2010 to 2018, the types of trauma were the motorcycle accidents in two cases and the other cases were fall, horse kick, and penetrating trauma. [1][2][3][4][5] It is notable that all patient in this series had anterior leaflet pathology. Blunt chest trauma accompanying the tremendous impact on the chest wall easily injures the anterior leaflet chordae and papillary muscle because the constructions are attached to the right heart free wall.…”
Section: Discussionmentioning
confidence: 99%
“…In the review of five surgical cases reported in Japan from 2010 to 2018, the types of trauma were the motorcycle accidents in two cases and the other cases were fall, horse kick, and penetrating trauma. [1][2][3][4][5] It is notable that all patient in this series had anterior leaflet pathology. Blunt chest trauma accompanying the tremendous impact on the chest wall easily injures the anterior leaflet chordae and papillary muscle because the constructions are attached to the right heart free wall.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, anterior leaflet chordal rupture is the most common finding. In addition, avulsion of the chordae or papillary muscles can cause TR [3,4]. Finally, a part of the tricuspid leaflet can be detached from the annulus, causing severe TR [5].…”
Section: Discussionmentioning
confidence: 99%
“…A few case reports have described the use of echocardiography for diagnosing wall motion abnormality in the setting of myocardial infarction and coronary artery dissection after blunt chest trauma, especially when myocardial contusion mimics myocardial infarction with elevated cardiac troponins [42,58]. Prompt identification of wall motion abnormality in coronary artery distribution following blunt chest trauma is important for the identification and treatment of coronary artery dissection.…”
Section: Us Echocardiography Transesophagealmentioning
confidence: 99%